DESIGN OF A ROBOTIC EXO-SUIT FOR KNEE LATERAL SUPPORT WITH AN INTERACTION CONTROL BASED ON RELATIVE MOTION ANGLE - Tanyildizi, Alper K.; Tasar, Beyda; Yakut, Oguz (World Scientific Publ Co Pte Ltd, 2022)
In this study, we focused on the design and control of a single DoF laterally supported knee exoskeleton robot designed to improve the load-carrying and strength capacity of healthy individuals, especially soldiers and workers. First, a nonlinear second-order differential model of the robotic knee orthosis was produced. Then, a single degree of freedom exoskeleton robot was designed and manufactured. An interactive motion control method based on the relative angle measurement principle between the knee joint of the user and the exo-suit knee joint was proposed. The user's knee joint motion is detected via an IMU sensor, and a controller was provided to allow the exo-suit to track the human knee joint in synchrony. In this study, a conventional PID, SMC, and moving surface SMC controllers were designed, and the controllers' performance were tested in real-time experiments. The maximum tracking errors in the PID, SMC, and MSMC controllers were 2.631(circle), 1.578(circle), and 1.289(circle), respectively, and the average tracking time errors were 0.10, 0.08, and 0.06 s, respectively. In addition, the designed and produced knee orthosis weighs 2.5 kg, making it one of the lightest and most compact designs for use by healthy individuals. The knee orthosis was made of steel, and thus it is very durable for use in all kinds of terrain conditions (military, industrial, etc.). Experimental findings about the proposed design and control method are analyzed in the results and discussion section.
Keywords: Knee exo-suit; interaction control; dynamic model of knee and shank; PID; SMC; MSMC control